Kearifan lokal masyarakat desa Mulengen Tagulandang terhadap pengelolaan sumber daya ikan Cakalang - Membri, Requel Serent; Manoppo, Lefrand; Pamikiran, Revols Dolfi Ch; Luasunaung, Alfret; Sumilat, Deiske Adeliene; Longdong, Florence Verra (Journal of Capture Fisheries Science and Technology, 2025)
Mulengen Village, Tagulandang, has a tradition of managing cakalang fish (Katsuwonus pelamis) resources in a traditional manner. This tradition not only serves to meet economic needs but also reflects values of togetherness, respect for nature, and cultural heritage that have been upheld for decades, often regarded as a "people’s festival." This research aims to understand the application of local wisdom by the community in its management and the social and economic impacts resulting from the decline in cakalang fish populations. The research findings indicate that the Mulengen Village community has a fisheries management system based on customary practices and local wisdom. The local wisdom of the community is manifested in the practice of catching cakalang fish using traditional fishing gear known as soma cakalang and Pamo-type boats, which is carried out collectively by the community. However, since 2019, cakalang fish have not been entering the village waters, leading to serious impacts on the livelihoods of the community. Social impacts include a decrease in collective activities and community togetherness, while economic impacts encompass the loss of primary income for fishermen and fishery entrepreneurs. This research emphasizes the importance of preserving local wisdom values in the management of fishery resources.